2012
DOI: 10.3945/jn.111.156968
|View full text |Cite
|
Sign up to set email alerts
|

A Period 2 Genetic Variant Interacts with Plasma SFA to Modify Plasma Lipid Concentrations in Adults with Metabolic Syndrome

Abstract: Genetic variants of Period 2 (PER2), a circadian clock gene, have been linked to metabolic syndrome (MetS). However, it is still unknown whether these genetic variants interact with the various types of plasma fatty acids. This study investigated whether common single nucleotide polymorphisms (SNPs) in the PER2 locus (rs934945 and rs2304672) interact with various classes of plasma fatty acids to modulate plasma lipid metabolism in 381 participants with MetS in the European LIPGENE study. Interestingly, the rs2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 41 publications
1
18
0
1
Order By: Relevance
“…Despite a small number of subjects, our results in the MS group suggest a link between PER2 and REV-ERB ALPHA genes with metabolic syndrome. Indeed, the associations between polymorphisms in the PER2 gene locus may influence lipid metabolism by interacting with total serum fatty acids [38]. One very interesting finding of the present work is the upregulation of the REV-ERB ALPHA gene in all cells fractions over the course of 24 h in VAT and its correlation with BMI and waist circumference.…”
Section: Discussionsupporting
confidence: 50%
“…Despite a small number of subjects, our results in the MS group suggest a link between PER2 and REV-ERB ALPHA genes with metabolic syndrome. Indeed, the associations between polymorphisms in the PER2 gene locus may influence lipid metabolism by interacting with total serum fatty acids [38]. One very interesting finding of the present work is the upregulation of the REV-ERB ALPHA gene in all cells fractions over the course of 24 h in VAT and its correlation with BMI and waist circumference.…”
Section: Discussionsupporting
confidence: 50%
“…These SNPs were located throughout the Per2 gene body and untranslated regions. Another study showed that in patients with metabolic syndrome, SNPs in the Per2 coding region were associated with higher mean plasma serum fatty acids [54]. Thus, Per2 appears to play an integral role in the regulation of ischemic adaptation in the heart and may also contribute to regulation of vascular function and metabolism.…”
Section: Period 2: Potential Role In the Heart Vasculature And In Mmentioning
confidence: 99%
“…83 Among individuals with metabolic syndromes and high levels of saturated fatty acid (SFA),-111G carriers have higher plasma lipid concentrations, 84 suggesting that the -111G/C allele interacts with plasma SFA to modify lipid levels.…”
Section: Per2mentioning
confidence: 99%